Effect of Organic and Inorganic Sources and Doses of Nitrogen Fertilizer on the Yield of Boro Rice (Journal of Environmental Science and Natural Resources, 2012)
The experiment was conducted to study the effect of different sources and doses of nitrogen application on the yield formation of  boro rice. Two indica modern boro rice varieties (BRRI dhan28 and BRRI dhan36) and 21 nitrogen fertilizer combinations were used in the experiment. The experiment was laid out in split- plot design with three replications by assigning varieties in the main plots and nitrogen fertilizers in the sub-plots. The unit plot size was 4m ? 2m. Yield and yield contributing characters were measured. Among the two varieties BRRI dhan28 produced higher grain and straw yield. Grain and straw yields were increased with the increase of nitrogen rate up to 120 kg ha-1 at all the sources. In general, organic manures alone could not produce higher grain yield but the combination of organic and inorganic fertilizers produced higher yield. The application of 60 kg N ha-1 as urea with 60 kg N ha-1as mustard oil cake (MOC) produced maximum grain and straw yield which was statistically similar to the yield of 50 kg N ha-1 as urea with 50 kg N ha-1 as MOC. The lowest values were found in control nitrogen application. The results suggest that replacement of 50% urea N by MOC was the best source of nitrogen considering higher yield of boro rice. Therefore,fertilization of BRRI dhan28 and BRRI dhan36 varieties of rice with 60 kg N ha-1 as urea and 60 kg N ha-1 as MOC or 50 kg N ha-1 as urea with 50 kg N ha-1 as MOC was found to be the best nitrogen rate among all the treatment combinations in respect of grain and straw yields. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11592 J. Environ. Sci. & Natural Resources, 5(1): 273- 282, 2012